2023
DOI: 10.1111/jce.15831
|View full text |Cite
|
Sign up to set email alerts
|

Network meta‐analysis and systematic review comparing efficacy and safety between very high power short duration, high power short duration, and conventional radiofrequency ablation of atrial fibrillation

Abstract: Background High‐power short‐duration (HPSD) atrial fibrillation (AF) ablation with a power of 40–50 W was proved to be safe and effective. Very high‐power short‐duration (vHPSD) AF ablation is a novel method using >50 W to obtain more durable AF ablation. This study aimed to evaluate the efficacy and safety of vHPSD ablation compared with HPSD ablation and conventional power ablation. Methods A literature search for studies that reported AF ablation outcomes, including short‐term freedom from atrial arrhythmia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Only one other NMA comparing the utility of vHPSD versus HPSD versus LPLD strategies exist 63 . On frequentist NMA, Tokavanich et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one other NMA comparing the utility of vHPSD versus HPSD versus LPLD strategies exist 63 . On frequentist NMA, Tokavanich et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other existing meta-analyses investigating vHPSD, HPSD, and LPLD Only one other NMA comparing the utility of vHPSD versus HPSD versus LPLD strategies exist. 63 On frequentist NMA, Tokavanich et al…”
Section: 2mentioning
confidence: 99%
“…These results re-emphasize that the TactiFlex SE is safe and effective for use in the treatment of paroxysmal AF in the full range of 20 to 50 W. Usage of the TactiFlex SE at power ranges ≥40 W may be more procedurally efficient and clinically effective than usage at lower powers. Previous meta-analyses have concluded that there is no difference in the safety risk profile between high power, short duration (HPSD) (≥40 W) and low power, long duration (<40 W), 17 , 18 and that HPSD may have a lower risk of esophageal thermal injury. 19 However, a recent randomized trial observed higher rates of asymptomatic cerebral emboli in the HPSD arm, 20 and if this observation is replicated additional study on the significance of these asymptomatic cerebral emboli may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…3 ) [ 34 ]. Moreover, a systematic review and metanalysis, including studies that compared vHPSD vs. HPSD ablation, showed similar efficacy and safety outcomes between the two approaches [ 35 ]. In preclinical studies, tissue temperatures achieved with HPSD ablation guided by ablation index (AI) have been reported as similar to those obtained with vHPSD ablation [ 36 ].…”
Section: Efficacy and Safety Of Hpsd Ablationmentioning
confidence: 99%